METODE DAKWAH DIGITAL DALAM KOMUNIKASI ISLAM UNTUK MENGUATKAN PEMAHAMAN KEISLAMAN GENERASI MILENIAL (AT-TAWASUL, 2023)
Digital dakwah has become one of the main methods of Islamic communication to strengthen Islamic understanding among millennial generation, which has different media preferences and learning methods compared to previous generations. This study aims to identify effective digital dakwah methods in enhancing Islamic understanding among millennials. The methodology used is library research, analyzing relevant literature on digital dakwah, Islamic communication, and millennial behavior in accessing information. The results show that digital dakwah, which prioritizes the use of visual and interactive platforms such as Instagram, YouTube, and TikTok, is more effective in reaching millennial audiences. Additionally, direct interaction and the timing of delivering messages are also important factors for successful digital dakwah. This research contributes by providing practical guidelines for preachers to utilize digital technology in bringing Islamic understanding closer to the millennial generation.